Langkah Strategis Menghadapi Situasi Ekonomi-Politik Indonesia - Edy Suandi Hamid (Unisia, 2012)
The importance of strategic policy in the area of political economy in among the significant factors determining the economic wellbeing of the society. The intervening variables that comes from various aspects within the country or global environment as well, also contribute to creation of economic stability. There are political flaws and global forces to be considered. Among political flaws in there are acute corruption mentality and high cost political process, where as among global forces are WTO and various funding institutions. The both aspects have led to the difficulty in maintaining a good economic wellbeing of the country. Amidst such condition, the importance of local culture should be properly recognized for the creation of a betel political situation. Again, a careful negotiation should also be initiated to persuade global forces in order, that global policies may not burdening domestic economic progress.